2021
DOI: 10.1186/s12889-021-11422-3
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence and socio-demographic associations of diet and physical activity risk-factors for cardiovascular disease in Bo, Sierra Leone

Abstract: Background Little is known about modifiable dietary and physical activity risk factors for cardiovascular diseases (CVDs) in Sierra Leone. This information is critical to the development of health improvement interventions to reduce the prevalence of these diseases. This cross-sectional study investigated the prevalence and socio-demographic correlates of dietary and physical activity risk behaviours amongst adults in Bo District, Sierra Leone. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…In a population with relatively low levels of overweight and obesity compared with many Western countries [33], the high prevalence of hypertension could be attributed to dietary behaviours related to salt intake. Salt intake is a key modifiable risk factor for hypertension and a recent study in Sierra Leonne found the prevalence of behaviours such as adding salt at the table or during cooking and eating salty snacks was high in adults ≥40 years [34]. We found that the effectiveness of care, as assessed by progression through the care cascade, was low with substantial dropout at the treatment and disease control stages.…”
Section: Discussionmentioning
confidence: 71%
“…In a population with relatively low levels of overweight and obesity compared with many Western countries [33], the high prevalence of hypertension could be attributed to dietary behaviours related to salt intake. Salt intake is a key modifiable risk factor for hypertension and a recent study in Sierra Leonne found the prevalence of behaviours such as adding salt at the table or during cooking and eating salty snacks was high in adults ≥40 years [34]. We found that the effectiveness of care, as assessed by progression through the care cascade, was low with substantial dropout at the treatment and disease control stages.…”
Section: Discussionmentioning
confidence: 71%
“…Public health education or removing/replacing salt shakers could also partially reduce salt added at the table [ 4 , 37 , 38 ]. However, the habit of adding salt at the table is prevalent, whether in developed regions [ 3 5 ] or in low- and middle-income countries [ 12 , 39 – 41 ]. Despite the cardiovascular benefits of reducing salt intake have been increasingly recognized, this has not fully translated into salt reduction action.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the proportion of people living in large cities has increased dramatically in recent decades and is expected to increase further; during the 20th century, the proportion of people living in urban areas rose from 14% to 50% [ [18] , [19] , [20] , [21] ]. This process of urbanization, that is, the growth of cities in terms of population and physical size [ [22] , [23] , [24] , [25] ], began a few centuries ago and was triggered by the invention of electric light in 1879 by Thomas Edison, during the industrial revolution.…”
Section: Discussionmentioning
confidence: 99%